Teaching English as a Foreign Language: Making Use of Spontaneous Language - Meiga Rahmanita; Nur Mukminatien (Jurnal Pendidikan Humaniora, 2019)
Abstract: Although the importancee of teaching and learning English has been widely recognized, many still do not know the best way to optimize the students’ ability in EFL learning. This article attempts to explore effective ways of teaching English by reviewing an article by Illèss and Akcan. In-volving 25 pre-service English teachers in Turkey and nine in Hungary, the researchers recorded their classrooms’ condition and conducted semi-controlled interviews with the teachers to investigate the use of real-life language in their classrooms. It was revealed that the use of real life language in EFL classrooms was beneficial to optimize students ability in EFL learning. In addition, facilitating the use of spontaneus language, providing authentic materials and real-life context, and creating learner-centered process of learning in the classrooms also affirmed the optimization. Key Words: english teaching pedagogy, spontaneous language, authentic teaching, traditional way of teachingAbstrak: Meskipun pentingnya pengajaran dan pembelajaran bahasa Inggris telah dikenal secara luas, dan banyak yang belum memahami cara terbaik untuk mengoptimalkan kemampuan siswa dalam belajar Bahasa Inggris. Artikel ini menguraikan cara-cara efektif dalam mengajar bahasa Inggris dengan menelaah artikel oleh Illèss dan Akcan. Melibatkan 25 calon guru Bahasa Inggris di Turki dan sembilan di Hongaria, peneliti merekam situasi kelas dan melakukan wawancara semi-terstruktur terhadap mereka. Telaah ini menemukan bahwa penggunaan bahasa yang digunakan secara alami di kelas pembelajaran bahasa Inggris bermanfaat untuk mengoptimalkan kemampuan siswa dalam belajar bahasa Inggris. Selain itu, memfasilitasi penggunaan bahasa secara spontan, menyiapkan materi otentik dan terkait konteks kehidupan nyata, serta menciptakan proses pembelajaran yang berpusat pada siswa juga membantu optimalisasi itu.Kata kunci: pedagogi pengajaran bahasa inggris, bahasa spontan, pengajaran otentik, cara pengajaran tradisional